Impact of radiotherapy on secondary lung cancer risk and survival in elderly female breast cancer survivors - Jieming Lu; Zhimin Shen; Xiaoqing Wang; Yanhong Lin; Ziyang Han; Mingqiang Kang (Translational Oncology)
This retrospective cohort study using SEER data from 2000 to 2020 examines the impact of radiotherapy on the risk of Secondary Primary Lung Cancer (SPLC) in 224,396 elderly female breast cancer survivors. Patients treated with radiotherapy displayed a 31 % increased SPLC risk compared to those not treated. Utilizing Cox Proportional Hazards and Poisson regression models, the study assessed various factors including age, race, and tumor characteristics. Propensity Score Matching (PSM) was employed to balance cohorts for survival analysis, which revealed that radiotherapy did not negatively impact overall survival despite the increased risk of SPLC. A nomogram was developed to aid clinical decision-making by predicting survival outcomes. The findings advocate for personalized treatment strategies and continuous monitoring to manage potential long-term adverse effects effectively, highlighting the need for a balanced approach in the treatment of breast cancer survivors.